Advertising restrictions regarding food of low nutritional value and the dependence on gambling - João SOUSA (Revista Jurídica Portucalense, 2022)
Advertising is a medium that not only informs, but also influences consumers, and, therefore, is a tool of great importance in our society, namely regarding the country’s economic development. However, the impact of advertising can also be negative and hence, it’s imperative to establish some restrictions. Concerning childhood obesity, which affects a great number of children worldwide, we found that the advertising of unhealthy food largely contributes to that alarming situation. Moreover, gambling addiction, which often emerges as a consequence of advertising itself, is connected to a false promise of overnight financial independence, leading people to risk the (little) money they have in order to obtain a reward that, while tempting, is unrealistic and, as such, affects not only the subjects themselves, but also those around them. With this article we aim to shed some light on advertising law, to draw attention to the impact it has on society and to the importance of implementing restrictions. Therefore, we seek to demonstrate that the current legal framework may be insufficient in order to solve the problems inherent to the advertising objects we have been referring to.